PERANCANGAN MEDIA PROMOSI MAGENTA COKLAT CAKE SHOP DALAM BENTUK WEB DESIGN - FEBRI TRI ADINDA Dra. Lisa Widiarti, M.Sn, Hendra Afriwan, S.Sn, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Magenta Coklat Cake Shop is one of the cake shop in the city of Padang and established in 2006. It is started from producing Praline is made of chocolate candies containing nuts, fruits, blueberry and so on. In 2008, then Magenta Coklat Cake Shop made the brownies according to the wishes of consumers. Magenta Coklat is not only to provide the cake, but also provide dessert. The promotion that ever conducted is through the medium of newspapers. However, because of the times, among teenagers and college students that are the target audience of Magenta Coklat have rarely read a newspaper, so the use of news media does not quite reach the required target audience, as more newspapers enjoyed by the collar, so that only a few people know. For that reason, there needs to be considerable media campaign through the media to reach the market are quite influential in the lives of the Padang people last few years.Keywords : promotion, Magenta Coklat Cake Shop, website